2007
DOI: 10.1111/j.1939-1676.2007.tb03055.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carvedilol Treatment in Dogs with Chronic Mitral Valvular Disease

Abstract: Background: Stimulation of the sympathetic nervous system occurs during the development of heart failure in dogs with chronic mitral valvular disease (CMVD).Hypothesis: The use of beta-blockers to modulate the activation of the sympathetic nervous system would be useful in dogs with CMVD.Animals: Group A included 13 dogs who received the conventional treatment (digoxin, benazepril, a reduced sodium diet, and codeine, and a diuretic when indicated), and group B included 12 dogs who received the protocol above p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…20 Carvedilol is currently used by some veterinarians in preclinical CVD and other cardiac diseases, however dosing is variable. 21,22 Evaluation of the baseline data in the current study confirms that although 87% of the dogs were Stage B2, they were for the most part quite early in this stage. Median LA:Ao(M-mode) was just above the normal reference range and the LA:Ao(2D) was within the normal range.…”
Section: Discussionsupporting
confidence: 82%
“…20 Carvedilol is currently used by some veterinarians in preclinical CVD and other cardiac diseases, however dosing is variable. 21,22 Evaluation of the baseline data in the current study confirms that although 87% of the dogs were Stage B2, they were for the most part quite early in this stage. Median LA:Ao(M-mode) was just above the normal reference range and the LA:Ao(2D) was within the normal range.…”
Section: Discussionsupporting
confidence: 82%
“…The tendency toward a decrease in systolic BP observed in the two subgroups treated with carvedilol may be associated with its vasodilatory effect, and an increase in the number and contractile force of cardiomyocytes ( 4 , 12 ,). However, the reduced values of systolic BP at T2 in subgroup II (carvedilol plus conventional therapy plus exercise training) were not significantly different from the results obtained for subgroup I (without carvedilol), meaning the addition of the beta-blocker to the therapy was not an obstacle to participation in an exercise training program.…”
Section: Discussionmentioning
confidence: 98%
“…Our preliminary paper demonstrated improvements in quality of life and functional class and a decrease in blood pressure (BP) in CMVD dogs after 3 months of carvedilol treatment ( 12 ). Recent studies of human heart failure have shown that an exercise protocol including regular aerobic physical training may be helpful for sympathetic tonus modulation.…”
Section: Introductionmentioning
confidence: 93%
“…118e120 A small, randomized, placebo-controlled, blinded study comparing low dose (0.3 mg/kg twice daily) carvedilol plus standard therapy to standard therapy only, showed a low rate of adverse side reactions. 118 Another, comparing findings in dogs receiving metoprolol to those not receiving a BARA, reported that, while the majority of dogs tolerated the addition of metoprolol in a step-wise fashion, it was necessary to discontinue the drug in approximately 25% of the dogs because of suspected side-effects. It is interesting that discontinuation of treatment was not more likely in dogs with pre-existing congestive heart failure.…”
Section: Acvim Class C2mentioning
confidence: 98%